Management of Drought Disaster in Indonesia - Andi Mursidi; Deffi Ayu Puspito Sari (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2017)
The drought disaster in Indonesia has occurred since 1811. Indonesia with tropical climate is highly sensitive to the climate anomaly El-Nino Southern Oscillation (ENSO) which is a source of drought. In addition to El Nino, the drought in Indonesia is also influenced by positive Indian Ocean Dipole (IOD) which constitute a regional climate phenomenon in Indian Ocean. The drought has widespread, complex impacts which lasts for a long time after the drought itself ends. This widespread impact lasting for so long is caused by the fact that water is a basic need and vital for every living creature, irreplaceable by any other resources. The impacts in agriculture sector include limited irrigation water, reduced planting areas, decreased land productivity, declined crops production, and less farmer’s income, and from social perspective, the drought disaster may promote division and conflict which expand to include the conflict between water users and even between (local) governments. This paper summarizes efforts in managing drought disaster in Indonesia from the context of disaster management cycle.